STUDY OF CUSTOMS AND SOCIAL WAYS OF THE HINDU SOCIETY OF THE THIRTIES IN MULK RAJ ANAND'S TWO LEAVES AND BUD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Anand is certainly a great novelist whose representation of the world around him-of men and women like Bakha, Sohini, Gauri, Munoo, Gangu, Lalu, Anant and so on-is true to life and whose characters are real, but there are certain norms and patterns in his work which have been common to social realists all over the world. He has also created real female characters like Laxmi and Gauri in The Old Woman and the cow, Sohini in Untouchable Aqi in The village and Rukmini in The Road which are very much reak.